Estudio de prefactibilidad para la instalación de una planta productora de fideos con harina de maíz morado (Zea mays L.) - Hinostroza Gastulo, Janire Kristell (2023)
The present investigation evaluates the technological, economic, financial, and social viability of the installation of purple corn flour (Zea Mays L.) spaghetti producing plant. The product will be aimed at people between 18 and 60 years old, belonging to socioeconomic level A and B in Lima Metropolitana. This would be sold in packages of 500 gr. through supermarkets such as Wong and Vivanda at a price of S/ 14,00 for the final consumer. The demand for the project would be 116 934 kg. of spaghetti for the last year of the project. Likewise, it was determined that the installed production capacity of the plant would be 229 592 kg of spaghetti per year. The proposed production process is based on the stages of sieving, mixing, and kneading, pressing, cutting, drying, cooling, and finally packaging and baling of the final product. The bottleneck of the process is the pressing station. To determine the location of the plant, the factor ranking method was used, where determining factors were used to evaluate the different alternatives for both macro-location and micro-location. In this way, it was defined that it would be in the Villa el Salvador, in the department of Lima, due to its proximity to the market. As for the plant layout, a total area of 528 m2 was determined, considering the production area, warehouses, administrative areas, and maneuvering yard. Finally, it was determined that the total investment required would be S/ 1 070 400,61, of which 60,25% would be our own contribution and 39,75% would be obtained through a bank loan. For this project there were obtained a NPV of 835 085,87 and IRR of 44,00%. Likewise, the calculated recovery period is 2 years and 11 months.